The Influence of Entrepreneurship Character Building and Leadership Spirit on The Economic Independence of Santri - Adriansah Adri; Hana Fatimatul Zahro; Fitriani Nursipa (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The issue of students’ limited economic independence within Islamic boarding schools has become a pressing challenge in developing self-reliance and preparing them for future livelihoods. Many students still rely heavily on external support, indicating the need for internal factors such as entrepreneurship character building and leadership spirit to be strengthened. This study aims to examine the influence of entrepreneurship character formation on students’ economic independence, the effect of leadership spirit on economic independence, and the combined impact of both factors in enhancing students’ economic resilience. This research employed a quantitative approach with simple random probability sampling. The population consisted of 472 students from three boarding schools—Al Jazary, Darussalam, and Mafatih Purwakarta—with a final sample of 83 respondents. Data were collected using structured questionnaires and analyzed through multiple linear regression using the Smart-PLS application. The findings revealed that both entrepreneurship character building and leadership spirit have a positive and significant influence on students’ economic independence, as indicated by P values below 0.05 (entrepreneurship character: 0.031; leadership spirit: 0.000). Furthermore, the R Square value of 0.742 with an adjusted R Square of 0.703 demonstrates that these variables jointly explain 70.3% of the variance in economic independence, signifying a strong effect. The F Square results further indicate that both entrepreneurship and leadership exert a medium effect size. This study contributes to the discourse on education and economic empowerment by highlighting how cultivating entrepreneurial character and leadership qualities within Islamic boarding schools can substantially enhance students’ economic independence